Integration of the Principles of Al-Ghunm bi Al-Ghurm and the Prohibition of Dhaman in Mudharabah: A Normative Analysis of DSN-MUI Fatwa No. 115/2017 - Edy Saputra; Amrizal Amrizal Hamsa; Mohammad Ridwan; Hamdanil; Putri Alya Sabina (Al-Hiwalah: Journal of Sharia Economic Law, 2026)
This study analyzes the integration of the principles of al-ghunm bi al-ghurm and the prohibition of liability on a trustee (al-amīn) in mudharabah contracts, particularly within DSN-MUI Fatwa No. 115/2017, and evaluates its consistency with contemporary Islamic financial practices. This research employs a normative legal approach using descriptive-analytical and interpretative methods based on library research of classical fiqh literature, legal maxims, fatwas, and relevant scholarly works. The findings reveal that both principles are conceptually integrated into a coherent normative framework governing risk allocation and liability, as reflected in the determination of profit-sharing ratios (nisbah), the prohibition of fixed returns, and the allocation of losses to the shahib al-māl except in cases of negligence, misconduct, or breach of contract. However, contemporary practices demonstrate significant deviations through guarantee mechanisms, profit smoothing, and risk-averse institutional strategies, which tend to shift the model from risk-sharing to risk transfer. The study contributes by proposing an integrated analytical framework that unifies these two legal maxims, which have largely been examined separately in previous studies, thereby offering a more systematic basis for evaluating Shariah compliance in mudharabah. It concludes that although the normative integration is well-established, its practical implementation remains inconsistent and requires stronger alignment between Islamic legal principles and institutional practices.